A compliant-mechanism-based lockable prismatic joint for high-load morphing structures. (December 2022) - Zhao, Yinjun; Hao, Guangbo; Chai, Luguang; Tian, Yingzhong; Xi, Fengfeng
Highlights: A novel design for compact, modular, normally lockable P joints is proposed. Compliant mechanisms and PZT stack are integrated for locking and releasing. Analysis and optimization model of the joint for locking applications are developed. The design is verified by nonlinear FEA and experimentally demonstrated. Abstract: Lockable joints are widely used in robotic systems and adaptive structures for energy management and/or topology reconfiguration. However, it is still challenging to design a joint with desired properties, including high locking load, infinite locking positions, short switching time, energy-efficient control, and a compact and lightweight structure. This paper aims at this open problem by presenting a novel piezoelectric (PZT) actuated lockable prismatic joint. This joint is a compliant mechanism (CM) consisting of a compound bridge-type compliant mechanism (CBCM) and a pair of compound multibeam parallelogram mechanisms (CMPMs). It can produce the required input/output stiffness to transmit large forces for high-load locking. It can also provide a desired input/output motion range for PZT actuation-based unlocking and for facilitating preloading adjustment. An analytical model is presented based on a compliance matrix method and the nonlinear model of the CMPM to predict the joint's static characteristics under various input/output conditions. A two-step optimization framework is proposed for locking applications. The theoretical study and nonlinear FEA/experimental verification confirm the feasibility of the design and the accuracy of the proposed model.